Sistem Informasi Dinas Kesejahteraan Rakyat Kabupaten Sumba Barat Daya Berbasis Web Menggunakan System Development Life Cycle - Stefanus Oktavinus Dairo; Cecilia D.P.B Gabriel; Dian Fransiska Ledi (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
The web-based Information System of the People's Welfare Service (DKR) of Southwest Sumba Regency is designed to improve efficiency in managing social welfare data and public services in the regency. This system is built using the System Development Life Cycle (SDLC) methodology, which includes seven main stages: planning, analysis, design, implementation, testing, maintenance, and evaluation. In the planning stage, system needs are identified to support various welfare programs, such as the distribution of social assistance and management of beneficiary data. The analysis stage focuses on collecting information to formulate system specifications that meet user needs. System design includes creating an intuitive user interface and an efficient database structure. Implementation is carried out by developing a web-based application that can be accessed by related parties to manage and monitor people's welfare programs. The testing stage aims to ensure that the system functions properly and according to needs. Maintenance is carried out periodically to ensure that the system continues to operate optimally along with the development of needs and technology. With the systematic implementation of SDLC, it is hoped that this system can improve data accuracy, transparency, and efficiency in managing social welfare programs in Southwest Sumba Regency.